(untitled) (International Journal of Medical and Surgical Sciences, 2023)
Acute appendicitis with situs inversus totalis is a rare type of acute abdominal pathology, with a prevalence of 1 in 10,000 births in the population. It has several embryological causes, with the most common being intestinal antirotation due to the involvement of the gene on chromosome 14. This clinical report describes the case of a 15-year-old adolescent patient who experienced 12 hours of abdominal pain, initially starting in the umbilical region and then migrating to the left iliac fossa. The pain was accompanied by an elevated temperature, nausea, and vomiting. During clinical examination, right cardiac auscultation, uncertain appendiceal signs, and peritoneal irritation were noted. Additionally, there was evidence of leukocytosis with neutrophilia. Tomography confirmed the complete dextroposition of abdominal and thoracic organs. An exploratory laparoscopy was performed, revealing macroscopic evidence of dextroposition of abdominal organs and uncomplicated appendicitis in the suppurative phase. The diagnosis of Acute Appendicitis with situs inversus totalis can be challenging due to its low prevalence and the presence of uncertain clinical signs. Therefore, the use of complementary examinations, such as computed axial tomography, is of utmost importance, along with visualization through diagnostic laparoscopy.